THE INFLUENCE OF SCARCITY MESSAGES AND PAY LATER PAYMENT METHOD ON IMPULSE BUYING BEHAVIOR OF GEN Z SHOPEE USERS IN MANADO - Sela, Syaloom Miracle; Saerang, David Paul Elia; Rogi, Mirah Helen (Universitas Sam Ratulangi, 2024)
This study examines the influence of Scarcity Messages and the Pay Later Payment Method on Impulse Buying Behavior among Gen Z Shopee users in Manado, specifically focusing on students of the Management Department at the University of Sam Ratulangi. The research aims to explore how these two marketing strategies affect the purchasing decisions of young consumers in the context of e-commerce. Utilizing a quantitative approach, data was collected through a structured questionnaire distributed to 100 respondents selected using purposive sampling. The data were analyzed using multiple regression analysis. The results reveal that both Scarcity Messages and the Pay Later Payment Method have a significant and positive impact on Impulse Buying Behavior, both partially and simultaneously. This research contributes to the understanding of how e-commerce platforms can leverage marketing strategies to influence consumer behavior, particularly among Gen Z. Keywords: Scarcity Messages, Pay Later Payment Method Impulse Buying Behavior.